Determinant of Social Cohesion: Ethnographic Studies of Minority-Majority Relations in the Jombang Community, Indonesia - Abidin, Achmad Anwar (International Journal of Law and Society, 2025)
This study explores the drivers of social cohesion in Jombang, Indonesia, with a particular focus on how minority-majority relations contribute to the region's capacity to serve as a model of peaceful coexistence in a diverse and post-conflict environment. The study aims to identify and analyse the socio-cultural factors underlying cohesion, emphasising the management of diversity as both a challenge and an opportunity for community resilience. Using a qualitative ethnographic methodology, data were collected through in-depth observation, interviews, and document analysis. The findings highlight four key drivers: the historical context of the arrival and development of religion, the role of family dynamics, group perspectives on religious understanding, and the influence of leadership as key factors in shaping social cohesion in the Jombang community. The study concludes that social cohesion in Jombang is not simply a product of cultural diversity but is actively maintained through shared historical narratives, intergenerational values, and inclusive leadership. However, this study is limited by its focus on a single geographic region, which may limit the generalizability of the findings. Nonetheless, this study offers practical implications by demonstrating how local cohesion strategies can inform policymaking, conflict resolution, and community development in other communities, as well as promote peaceful, just, and inclusive societies, as mandated by SDG 16 (Peace, Justice, and Strong Institutions). The study's originality lies in its ethnographic lens, which reveals nuanced mechanisms of cohesion, providing both academic value and practical lessons for strengthening intergroup harmony in plural contexts.